Online System Policy And Cyber Notary In Facing The Impact Of Covid-19 - Ahmad Farid Bisyarohatie; Umar Ma'ruf; Widhi Handoko (Sultan Agung Notary Law Review, 2022)
The purpose of this study is to describe and explain the reasons for the implementation of the online system and Cyber Notary has not been held in relation to Legal Policy in Facing the Impact of Covid-19 on Notary Performance. Describe the obstacles faced and to provide solutions to notaries in implementing an online and cyber notary system in Facing the Impact of Covid-19 on Notary Public Performance.The approach method in this research is juridical empirical. The specification used in this research is descriptive analytical. The data analysis method was carried out qualitatively. The results of this study are the application of an online system to cyber notary in Surakarta, which still requires more in-depth dissemination of security and effectiveness in the use of online systems and cyber notaries, as well as the obstacles faced in implementing the online system and cyber notary policies in dealing with the impact of covid- 19 in the city of Surakarta, there are still conflicting rules between Article 15 UUJN and Article 16 UUJN, linked to Articles 11 and 12 of Act No. 11 of 2008 and Act No. 19 of 2016 concerning Electronic Information and Transactions (UU ITE and PUU ITE).